A mechanism-driven strategy for in-silico prediction, molecular docking, synthesis, and biological assessment of substituted 1,3,4-oxadiazole derivatives as novel antidiabetic agents - Patidar, Mohini; Dubey, Raghvendra; Minz, Sunita; Pradhan, Madhulika; Deshmukh, Nitin (Creative Pharma Assent, 2025)
Background: Diabetes mellitus is a long-standing and debilitating metabolic condition that imposes a substantial global health burden, leading to severe and widespread complications. Objectives: This study aims to predict physicochemical properties of 1,3,4-oxadiazole derivatives using in-silico methods and molecular docking simulations to explore their potential as α-glucosidase inhibitors for diabetes management. Furthermore, this study aims to experimentally synthesize and characterize these derivatives to validate their inhibitory activity. Methods: In silico drug-likeness, pharmacokinetic, and toxicity profiling of substituted oxadiazole derivatives were performed using the Molinspiration and PreADMET web tools. Molecular docking simulations were conducted with the target protein alpha-glucosidase (PDB ID: 3WY1) to assess its anti-diabetic potential. This study suggests that oxadiazole has the potential to be a novel anti-diabetic agent. Results: Compound 3a1 formed 5 significant hydrogen bonds with Gly228, Thr226, Leu227, Tyr235, Glu271 with docking scores of -156.118 and re-rank scores of -91.600 comparable to the standard drug Miglitol, which formed 6 hydrogen bonds Val380, Asp401, Lys398, Gly399, Glu377, Asp379 but had lower docking and re-rank scores (-69.4415 and -95.887). Based on docking results, five oxadiazole derivatives were synthesized via Mannich base cyclization, yielding 62.2 – 79.9%. They showed moderate to excellent anti-diabetic activity, with compounds 3a1 and 3a3 demonstrating no toxicity or mortality at 40 mg/kg oral dose. Conclusion: Our study highlights that the oxadiazole pharmacophore is a key structural motif for the development of potential anti-diabetic compounds